Research Progress of Small Molecule VEGFR/c-Met Inhibitors as Anticancer Agents (2016–Present) - Qian Zhang; Pengwu Zheng; Wufu Zhu (Molecules, 2020)
Vascular endothelial growth factor receptor 2 (VEGFR-2) binds to VEGFR-A, VEGFR-C and VEGFR-D and participates in the formation of tumor blood vessels, mediates the proliferation of endothelial cells, enhances microvascular permeability, and blocks apoptosis. Blocking or downregulating the signal transduction of VEGFR is the main way to discover new drugs for many human angiogenesis-dependent malignancies. Mesenchymal epithelial transfer factor tyrosine kinase (c-Met) is a high affinity receptor for hepatocyte growth factor (HGF). Abnormal c-Met signaling plays an important role in the formation, invasion and metastasis of human tumors. Therefore, the HGF/c-Met signaling pathway has become a significant target for cancer treatment. Related studies have shown that the conduction of the VEGFR and c-Met signaling pathways has a synergistic effect in inducing angiogenesis and inhibiting tumor growth. In recent years, multi-target small molecule inhibitors have become a research hotspot, among which the research of VEGFR and c-Met dual-target small molecule inhibitors has become more and more extensive. In this review, we comprehensively summarize the chemical structures and biological characteristics of novel VEGFR/c-Met dual-target small-molecule inhibitors in the past five years.